2009
DOI: 10.1111/j.1526-4610.2009.01409.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocardial Infarction With Sumatriptan: A Case Report and Review of the Literature

Abstract: We report a case of myocardial infarction associated with the use of sumatriptan and review the literature regarding similar cases. A 54-year-old woman with a history of migraine without aura, mild arterial hypertension, depression, and no history of coronary artery disease was admitted to our hospital for acute myocardial infarction, 30 minutes after using 6 mg of subcutaneous sumatriptan. Coronary angiography performed several days later revealed a normal coronary arterial system. Although at discharge the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
(12 reference statements)
1
11
0
1
Order By: Relevance
“…[19][20][21][22] In a review in 2009, 21 cases were described in which a cardiac event occurred after oralor subcutaneous injection of triptans. 23 In many of these events, however, the time of the cardiac event was outside the therapeutic window (5 half-lives) of the triptan in question.…”
Section: Migraine and Coronary Heart Diseasementioning
confidence: 99%
“…[19][20][21][22] In a review in 2009, 21 cases were described in which a cardiac event occurred after oralor subcutaneous injection of triptans. 23 In many of these events, however, the time of the cardiac event was outside the therapeutic window (5 half-lives) of the triptan in question.…”
Section: Migraine and Coronary Heart Diseasementioning
confidence: 99%
“…However, since the expected treatment regimen for acute migraines only involves the ED setting, no such events have been reported [22]. In contrast to other recommended treatments, the adverse effect profile of metoclopramide is less worrisome than that of triptans (hypertensive crisis and myocardial infarction), which is also highly used in the ED setting [23-24]. Studies have also shown that the dose of metoclopramide necessary to achieve 48 hours of sustained freedom from pain was no different in patients receiving 10, 20, or 40 mg; thus, the smallest dose of 10 mg, plus 25 mg of diphenhydramine (dyskinesia prophylaxis), is effective in treating acute migraines [20].…”
Section: Reviewmentioning
confidence: 99%
“…He had had no personal or family history of cardiovascular disease or risk factors for it, but coronary angiography revealed total occlusion of the left anterior descending artery (LAD) 32 . Another patient suffered an acute MI while using sumatriptan who was found to have normal coronary arteries at cardiac catheterization 33 . These, arguably, are just 2 isolated cases, but there are not large numbers of patients with cardiovascular events while on headache medications to investigate.…”
Section: The Role Of Cardiovascular Screening In Headache Patientsmentioning
confidence: 99%